Efektivitas Pajak Karbon sebagai Strategi Mitigasi Perubahan Iklim Perspektif Hakim Pajak di Indonesia - Lintang Rayi; Rahayu Subekti; Sapto Hermawan (PLEDOI (Jurnal Hukum dan Keadilan), 2024)
This research analyzes the passing of regulations imposing a tax on carbon, discusses the effectiveness of implementing a carbon tax as well as the knowledge and opinions of tax judges regarding these regulations. Carbon emissions have a big influence on climate change, the more carbon emissions increase, the worse the environment becomes and is detrimental to all creatures on earth, therefore it is important to immediately reduce carbon emissions and control climate change. Seeing that Finland, Sweden and other countries have succeeded in reducing carbon gas emissions by implementing a carbon tax, the government decided to implement a carbon tax in Indonesia in the hope that it will reach the point of net zero emissions in accordance with the agreement in the Paris Agreement. In implementing a policy there must be regulations, for carbon taxes, the law enforcement will be enforced by the tax court. Tax judges must understand about Carbon Tax. By conducting this research, it is known that the differences in opinion of each judge mean that not all judges agree with the implementation of the carbon tax.